(untitled) (The Conference Hub, 2025)
This article focuses on the enormous potential of women’s entrepreneurship in the service sector. Women’s entrepreneurship demonstrates a high level of initiative and willingness to take responsibility, but the issues of facing a lack of financial resources, information support, and practical knowledge are studied and suggestions and recommendations are made.